Analisis Isi Nilai Edukatif Pada Novel Jilbab Pertamaku Karya Asma Nadia Dan Pemanfaatanya Dalam Pembelajaran Sastra Pada Kelas XI Di SMK - Santi Virdiasari (Universitas Negeri Padang, 2021)
This research discusses the analysis of the educational value in my first hijab nove, as well as its use in literary learning in class XI at SMK. The objectives to be achieved are to describe and analyze what educational values are contained in the novel Jilbab Pertamaku Karya Asma Nadia, which can applied in literary learning in class XI at SMK through the novel Jilbab Pertamaku. In this study using a descriptive narrative technique, with a qualitative approach to content analysis and the subject of this study is the novel Jilbab First by Asma Nadia. This research is focused on problems related to the educational value contained in the novel Jilbab Pertamaku, which is then adjusted to the application of students' daily lives. Data collection techniques and instruments used read and note while the instruments used data cards. The validity of the data was obtained through validity and reliability using source and intraratter triangulation. The results of this study indicate that the educational value contained in the novel Jilbab Pertamaku by Asma Nadia includes religious values, toughness, caring, and honesty. Of these four values, the novel Jilba First by Asma Nadia can be used as literary learning in class XI at SMK because the language in the novel is easy to understand, can be used as learning to apply educational values, is a reading that has good moral values. for students.